Caracterización de los materiales de subrasante en zonas no urbanizadas de la ciudad de Loja, aplicadas a obras de infraestructura vial en el polígono denominado “Salapa Central - Villavicencio Aldaz, Israel Santiago (2014)
This research theme aims to provide information on the physical and mechanical subgrade materials, through the development of two zoning maps depending on the bearing capacity and soil classification features present in the area study called "Salapa Central" located in sector Salapa Under the Loja city. So as the basis for the study and design of the upper layers such as sub-base and base, as well as the tread, applied to road infrastructure projects. Additionally this research was performed by extracting the samples every 250 to 500 m distance between each point, at depths of 0.50 m, 1.00 m and 1.50 m; where the characterization of the material was performed by the following laboratory tests: moisture content, consistency limits (LL, LP, IP), sieve analysis, modified proctor, CBR and abrasion breeding materials.